Acute paediatric mastoiditis in the UK before and during the COVID‐19 pandemic: A national observational study. (3rd November 2021) - Smith, Matthew E.; Jones, G. Huw; Hardman, John C.; Nichani, Jaya; Khwaja, Sadie; ,; Bruce, Iain A.; Rea, Peter
Abstract: Objectives: To explore the impact of COVID‐19 on the management and outcomes of acute paediatric mastoiditis across the UK. Design: National retrospective and prospective audit. Setting: 48 UK secondary care ENT departments. Participants: Consecutive children aged 18 years or under, referred to ENT with a clinical diagnosis of mastoiditis. Main outcome measures: Cases were divided into Period 1 (01/11/19‐15/03/20), before the UK population were instructed to reduce social contact, and Period 2 (16/03/20‐30/04/21), following this. Periods 1 and 2 were compared for population variables, management and outcomes. Secondary analyses compared outcomes by primary treatment (medical/needle aspiration/surgical). Results: 286 cases met criteria (median 4 per site, range 0–24). 9.4 cases were recorded per week in period 1 versus 2.0 in period 2, with no winter increase in cases in December 2020‐Febraury 2021. Patient age differed between periods 1 and 2 (3.2 vs 4.7 years respectively, p  < 0.001). 85% of children in period 2 were tested for COVID‐19 with a single positive test. In period, 2 cases associated with P. aeruginosa significantly increased. 48.6% of children were scanned in period 1 vs 41.1% in period 2. Surgical management was used more frequently in period 1 (43.0% vs 24.3%, p  = 0.001). Treatment success was high, with failure of initial management in 6.3%, and 30‐day re‐admission for recurrence in 2.1%. The adverse event rate (15.7% overall) did not vary by treatment modality or between periods 1& 2. Conclusion: The COVID‐19 pandemic led to a significant change in the presentation and case mix of acute paediatric mastoiditis in the UK.